Pengembangan Bahan Ajar Komik Berbasis Flipbook untuk Meningkatkan Keterampilan Proses Sains Siswa Kelas V SD Negeri 2 Banda Aceh - Eka Yulianti; Sariakin Sariakin; Siti Mayang Sari (Lembaga Teewan Journal Solutions, 2026)
This study aims to develop a comic-based flipbook teaching material and to examine its validity, practicality, and effectiveness in improving elementary school students’ science process skills. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were 27 fifth-grade students of SD Negeri 2 Banda Aceh. Data were collected through observation, interviews, questionnaires, and learning outcome tests. The data were analyzed using descriptive quantitative and qualitative approaches. The results showed that the developed teaching material achieved a very high level of validity with an average score of 96%, categorized as highly valid. During the implementation stage, the use of the comic-based flipbook increased students’ engagement and learning motivation. Furthermore, the evaluation results indicated an improvement in students’ learning outcomes, with the average score increasing from 57.4 in the pre-test to 82.4 in the post-test. In conclusion, the comic-based flipbook teaching material is valid, practical, and effective in enhancing students’ science process skills and can be used as an innovative alternative learning media in elementary